2022
DOI: 10.3390/app122412577
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Race Performance Characteristics for the 50 m and 100 m Freestyle among Regional-Level Male Swimmers

Abstract: Race analysis performed by faster and slower swimmers enables the definition of effective strategies for carrying out the competition. Until now, measurements of this type were mainly conducted among top-level athletes. The aim of the study was to determine the differences in swimming technique in sprint races between faster (FS) and slower (SS) regional-level swimmers. The performance of 33 swimmers (mean FINA points = 449) competing in 50 m and 100 m freestyle races was analysed. To determine the velocity (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…In addition, in the study from Wądrzyk et al [ 28 ], it was observed that both fast (mean FINA points for 100 m front crawl = 557) and slow (mean FINA points for 100 m front crawl = 379) international level swimmers had similar SR (fast swimmers = 49.78 ± 2.47 vs. slower = 49.21 ± 4.40 cycles/min −1 ) with our participants. Therefore, it could be hypothesized, that in swimming protocols which are oriented to a specific event distance, in this instance 100 m, swimmers show similar SR.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, in the study from Wądrzyk et al [ 28 ], it was observed that both fast (mean FINA points for 100 m front crawl = 557) and slow (mean FINA points for 100 m front crawl = 379) international level swimmers had similar SR (fast swimmers = 49.78 ± 2.47 vs. slower = 49.21 ± 4.40 cycles/min −1 ) with our participants. Therefore, it could be hypothesized, that in swimming protocols which are oriented to a specific event distance, in this instance 100 m, swimmers show similar SR.…”
Section: Discussionsupporting
confidence: 74%
“…Thus, this hypothesis possibly fits with the volume of a training set as well. In addition, Wądrzyk et al [ 28 ], showed that in a 100 m front crawl, swimmers had greater SI than the 50 m and this hypothesis may fit with the volume of each repetition of the training set. These findings seem contradictory; however, they do demonstrate that swimming distance most likely affects SI, but not in a particular manner.…”
Section: Discussionmentioning
confidence: 99%
“…Swimming races are defined to integrate sprint distances (50–100 m), middle distances (200–400 m), and long distances (800–1500 m) [ 9 ], with more or less 86% of indoor swimming events being performed at maximal or supramaximal intensities [ 10 ]. Hence, the accuracy in identifying exercise intensity domains toward the optimization of daily training plays an important role in performance enhancement in swimming [ 11 ], by athletes with appropriate body composition and high physical capacity corresponding to the specificity of the aquatic effort [ 4 ].…”
Section: Introductionmentioning
confidence: 99%